30.3k views
5 votes
Solve the equation 5.3g+9=2.3g+15.

2 Answers

2 votes

g=2

5.3g+9−2.3g=2.3g+15−2.3g

3g+9=15

3g+9−9=15−9

3g=6

3g/3=6/3

therefore, g=2

hope i helped ^__^

User Ateeq
by
5.4k points
3 votes

Answer:

The solution for the equation is
g=2.

Explanation:

Consider the provided equation.


5.3g+9=2.3g+15

Subtract 2.3g from both sides.


5.3g-2.3g+9=2.3g-2.3g+15


3g+9=15

Subtract 9 from both sides.


3g+9-9=15-9


3g=6

Divide both sides by 3.


(3g)/(3)=(6)/(3)


g=2

Hence, the solution for the equation is
g=2.

User FuzzyDuck
by
6.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.